Pengaruh Pembelajaran Berbasis Proyek terhadap Kemampuan “4C” Siswa Sekolah Dasar pada Masa Pandemi - Donna Avianty; Sari Mellina Tobing (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2022)
Today's world is competing to create and utilize technology and information. The rapid development of world civilization is also a challenge for the world of education. To prepare for this, education is expected to design and implement learning that can encourage the skills needed in the 21st century. Some of the skills needed to face the challenges of the 21st century are communication, collaboration, critical thinking, and creative thinking (4Cs). Project-based learning is one of the learning methods that does not only focus on results, but also pays attention to every process that occurs, and is believed to be able to encourage the desire to research and ability to solve problems, think creatively and critically, and increase the collaboration and communication power of students. This study proves that the effect of projectbased learning on improving the 4C ability of students Grade V SDKr. Shining Star has a 84.7% Of success rate. This is shown during the learning process students are able to discuss with peers in group members and state that working with groups is more effective than working independently, besides that students are also able to present problem solving and produce products that are in accordance with the plans made by the group. The research method used is descriptive qualitative which makes 12 students as research subjects.